Near-threshold fatigue crack growth behavior of 10% Cr martensitic steel welded joint with 9% Cr weld metal in high temperature air. (August 2020) - Sun, Qixing; Li, Kejian; Li, Xiaogang; Rui, Shao-Shi; Cai, Zhipeng; Pan, Jiluan
Highlights: The Δ K th tests of a 9%–12% Cr steel welded joint were firstly performed in 538 °C air. The weld metal with the lowest Cr content had the highest Δ K th . The heat affected zone with fine grains and few laths had lower Δ K th than base metal. The Δ K th differences and stress ratios' influences were explained by crack closures. Oxide-induced crack closure of the weld metal was still influential at R = 0.7. Abstract: The near-threshold fatigue crack growth (FCG) behavior under different stress ratios (R) of a 9%–12% Cr steel welded joint was studied in 538 °C air. The most significant oxide-induced crack closure (OICC) occurred in weld metal (WM) due to the lowest Cr content, resulting in the highest threshold value (Δ K th ) of WM. The base metal (BM) with coarser grains and denser lath structures had more obvious roughness-induced crack closure (RICC) and more severe crack deflection, which led to a higher Δ K th of BM than heat affected zone (HAZ). The Δ K th of WM, HAZ and BM decreased as R increased.